Profiling of Polyphenol Composition and Antiradical Capacity of Erica cinerea - Alfredo Aires; Rosa Carvalho (MDPI AG, 2017)
The aim of the current study was to determine the profile and content of polyphenols present in Erica cinerea, an important plant species from Northern Portuguese flora and often reported as having anti-inflammatory, antioxidant, and anti-radical activity. The analysis of polyphenols was performed by HPLC-DAD/UV-Vis, and the 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) method was used to evaluate its radical scavenging activity. HPLC analysis showed that both plants presented a great diversity of compounds, with 33% flavones, 28% flavanols, and 26% hydroxycinnamic acids. The antiradical activity was dose-dependent, and the IC50 values were 0.251 mg mL−1. Based on our study, E. cinerea presented interesting bioactive compounds and it can be used to extract and purify bioactive polyphenols to be used in pharmaceutical or agro-food industries.